Construction of 1T-MoS2 quantum dots-interspersed (Bi1−xFex)VO4 heterostructures for electron transport and photocatalytic properties. Issue 22 (7th April 2021) - Sajid, Muhammad Munir; Zhai, Haifa; Shad, Naveed Akhtar; Shafique, Muhammad; Afzal, Amir Muhammad; Javed, Yasir; Khan, Sadaf Bashir; Amin, Nasir; Zhang, Zhengjun
Abstract : The present study reports trigonal phase molybdenum disulfide quantum dots (MoS2 /QDs)-decorated (Bi1− x Fe x )VO4 composite heterostructures. Abstract : The present study reports trigonal phase molybdenum disulfide quantum dots (MoS2 /QDs)-decorated (Bi1− x Fe x )VO4 composite heterostructures. Initially, (Bi1− x Fe x )VO4 heterostructure nanophotocatalysts were synthesized through the hydrothermal method decorated with 1T-MoS2 via a sonication process. 1T-MoS2 @(Bi1− x Fe x )VO4 heterostructures were characterized in detail for phase purity and crystallinity using XRD and Raman spectroscopy. The Raman mode evaluation indicated monoclinic, mixed monoclinic-tetragonal and tetragonal structure development with increasing Fe concentration. For physiochemical properties, SEM, EDX, XPS, PL, EPR, UV-visible and BET techniques were applied. The optical energy band gaps of 1T-MoS2 @(Bi1− x Fe x )VO4 heterostructures were calculated using the Tauc plot method. It shows a blue shift initially within a monoclinic structure then a red shift with an increase of Fe concentration. 1T-MoS2 @(Bi40 Fe60 )VO4 with 2 wt% of 1T-MoS2 -QDs carrying a mixed phase exhibited higher photocatalytic activity. The enhanced photocatalytic activity is attributed to the higher electron transportation from (Bi1− x Fe x )VO4 surface onto 1T-MoS2 surface, consequently blocking the fast electron–hole recombination within (Bi1− x Fe x )VO4 . 1T-MoS2 co-catalyst interaction with (Bi1− x Fe x )VO4 enhanced the light absorption in the visible region. The close contact of small 1T-MoS2 -QDs with (Bi1− x Fe x )VO4 develops a high degree of crystallinity, with fewer defects showing mesoporous/nanoporous structures within the heterostructures which allows more active sites. Herein, the mechanism involved in the synthesis of heterostructures and optimum conditions for photocatalytic degradation of crystal violet dye are explored and discussed thoroughly.